Home Wi-Fi mesh networking technology - Longjie XU; Ning GUO; Tao GUO; Jianting HAN (Dianxin kexue)
Wi-Fi mesh is a kind of suitable for large or complex home wireless self-organizing network solution.It can provide users with full coverage,self-handoff and easy installation of high-quality wireless network.Wi-Fi mesh has many advantages,such as self-organizing,self-management,self-repair and self-balance.But the existing Wi-Fi mesh product implementation scheme is not uniform,complex,high terminal capability requirement and unable to interoperate.The realization of multi AP collaborative work in home network was firstly discussed,then the main current technology development of Wi-Fi mesh was analyzed,and the technical scheme and comparative analysis of home Wi-Fi mesh was focused on.Then,aiming at home application scenario,a Wi-Fi mesh technology implementation scheme for operators was presented,which was modularized,easy to realize,with low terminal capability requirement and good interoperability.